AUDIT OPERASIONAL ATAS BIAYA PERJALANAN DINAS DAN TUGAS BELAJAR (STUDI KASUS PADA UNIVERSITAS XYZ) - Tarigan, Arya Gina; Carmel Meiden (Fundamental Management Journal, 2024)
The objective of the operational audit is to analyze whether the disbursement process and the cost accountability for official travel and study assignments have been running effectively and efficiently in accordance with the Standard Operational Procedure (SOP) in the university, and identify problems that arise as a result of the inefficiency and ineffectiveness of the accountability process at XYZ University. The research method used in this research is descriptive analysis by collecting data so that it can provide a fairly clear picture of the object under study to make conclusions. In addition, researchers collect and process the results of questionnaires related to internal control and conduct interviews with related parties. From the research conducted, it is known that the costs of official travel and study assignments are uncollectible advances that arise because there is no responsibility for these costs. Internal control over the provision of official travel costs and study assignments is considered effective, but accountability for these costs is considered less effective. Apart from this, the accountability for costs that have been incurred but canceled by means of returning the down payment is deemed inefficient. The main cause of the ineffectiveness and inefficient of this procedure is the lack of firmness in imposing sanctions on employees who do not carry out accountability for the costs of official travel and study assignments. The recommendations put forward by researchers need to be implemented by the university as a step towards improving the procedure for giving and accounting for costs for official travel and study assignments. Keywords: Operational Audit, Cost, Down Payment.